A REVIEW ON FORMULATION AND CHARACTERIZATION OF HERBOSOME COMPLEX - CHAUDHURY, IMDADUL HAQUE; DEB, PULAK; DAS, SUMIT (International Journal of Current Pharmaceutical Research, 2019)
The major amount of active constituents comprises in herbal drugs with excellent bioactivity in vitro but less in vivo because of their poor lipid solubility and improper size of the molecules. This results in poor absorption and bioavailability of active constituents from the herbal extract. Herbosome technology enhances the bioavailability of herbal extracts. Herbosome act as the bridge between the novel delivery system and conventional delivery system. It is a complex of natural active ingredients and phospholipids (phosphatidylcholine, phosphatidylserine etc.) which increases absorption of herbal extract. Herbosome is the novel emerging technique applied to phytopharmaceuticals for the enhancement of bioavailability of herbal extract for medicinal applications. This article overviews about herbosome technology, recent advance, their application for various standardized herbal extracts and aims to provide complete scientific information, characterization about herbosomes as a promising drug delivery system.